Maliki Interdisciplinary Journa Peran Ciri Kepribadian terhadap Pemanfaatan Layanan Kesehatan Mental Digital dalam Konteks Lintas Budaya: Analisis Konseptual tentang Integrasi Kepribadian dan Budaya dalam Adaptasi Teknologi Psikologis Modern - naizar, ricky kavino (Maliki Interdisciplinary Journal, 2025)
Digital mental health (DMH) is now a major breakthrough in meeting the growing global demand for psychological services. This article examines how personality traits influence individuals’ propensity to use digital-based mental health services across diverse cultural backgrounds. Using a conceptual analysis approach and systematic literature reflection, this article connects the Big Five personality theory, Eysenck’s model, and Rogers’ humanistic approach to explain the behavior of boldly seeking psychological help. The results indicate that openness and neuroticism positively influence the acceptance of digital services, while conscientiousness is related to the consistency of their use. Furthermore, cultural factors play a significant moderating role in influencing individuals’ attitudes toward utilizing digital mental health services. This article underscores the importance of developing digital interventions that are sensitive to local personality and cultural values ​​to reach a wider and more effective audience.